First metatarsal trabecular bone structure in extant hominoids and Swartkrans hominins. Issue 131 (June 2019) - Komza, Klara; Skinner, Matthew M.
Abstract: Changes in first metatarsal (MT1) morphology within the hominin clade are crucial for reconstructing the evolution of a forefoot adapted for human-like gait. Studies of the external morphology of the MT1 in humans, non-human apes, and fossil hominins have documented changes in its robusticity, epiphyseal shape and its articulation with the medial cuneiform. Here, we test whether trabecular structure in the MT1 reflects different loading patterns in the forefoot across extant large apes and humans, and within this comparative context, infer locomotor behavior in two fossil hominins from Swartkrans, South Africa. Microtomographic scans were collected from the MT1 of Pongo sp. (n = 6), Gorilla gorilla (n = 10), Pan troglodytes (n = 10), Homo sapiens (n = 11), as well as SKX 5017 ( Paranthropus robustus ), and SK 1813 (Hominin gen. sp. indet.). Trabecular structure was quantified within the head and base using a 'whole-epiphysis' approach with medtool 4.2. We found that modern humans displayed relatively higher bone volume fraction (BV/TV) in the dorsal region of each epiphysis and a higher overall degree of anisotropy (DA), whereas great apes showed higher BV/TV in the plantar regions, reflecting dorsiflexion at the metatarsophalangeal (MTP) joint in the former and plantarflexion in the latter. Both fossils displayed low DA, with SKX 5017 showing a hyper-dorsal concentration of trabecular bone in the head (similar to humans), while SK 1813 showed a more central trabecular distribution not seen in either humans or non-human apes. Additionally, we found differences between non-human apes, modern humans, and the fossil taxa in trabecular spacing (Tb.Sp.), number (Tb.N.), and thickness (Tb.th.). While low DA in both fossils suggests increased mobility of the MT1, differences in their trabecular distributions could indicate variable locomotion in these Pleistocene hominins (recognizing that the juvenile status of SK 1813 is a potential confounding factor). In particular, evidence for consistent loading in hyper-dorsiflexion in SKX 5017 would suggest locomotor behaviors beyond human-like toe off during terrestrial locomotion.